Gardens as resources in advanced age in aotearoa NZ: More than therapeutic. (November 2021) - Wiles, Janine; Miskelly, Philippa; Stewart, Oneroa; Rolleston, Anna; Gott, Merryn; Kerse, Ngaire
Abstract: For older people gardens may be paradoxical sites. Whilst gardening is associated in multiple ways with wellbeing and health, gardens may also become a source of frustration and worry as ageing bodies limit gardening activities. Yet determination remains. However, little of the well-established body of work on gardens and old age includes people in advanced age. In this paper, we draw on interviews with Māori and non-Māori 85-90-year olds in Aotearoa, New Zealand, focusing on how they talk about their wellbeing in relation to past, present, and future experiences of home gardening. Our research shows home gardens and gardening figure prominently and positively in the narratives of people in advanced age. Most of our participants described themselves as active gardeners; most also lived with multimorbidity, sometimes severe and complex. Applying positioning theory, we examine how our participants connect gardens and gardening to identity; connectedness; and adaptation and renegotiation of health and wellbeing in ageing bodies. Home gardens are 'more than therapeutic'; while they are protective of health and wellbeing, they are also enabling places for the expression and performance of agency in advanced age. These understandings have practical implications for supporting wellbeing amongst those in advanced age. Highlights: Gardening links to health & well-being, but may also cause frustration & worry. We explore home gardening of people in advanced age including older indigenous people. Most participants identified as active gardeners; most lived with multimorbidities. They related gardening to identity, connectedness, & expressing agency in very old age. Home gardens protect health & are enabling places; they are therapeutic and more .